1992
DOI: 10.1056/nejm199201093260204
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload in Africa

Abstract: Iron overload in Africa may be caused by an interaction between the amount of dietary iron and a gene distinct from any HLA-linked gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Person with hemochromatosis (HFE) associated mutations may be on higher side of developing iron over load related oxidative stress and neuropathology with ingestion of daily iron supplement [31,37]. Metal metabolism is combined interplay between genes related with synthesis of metalloenzymes and dietary metal supplement.…”
Section: Neurodegenerative Diseases and Oxidative Stressmentioning
confidence: 99%
“…Person with hemochromatosis (HFE) associated mutations may be on higher side of developing iron over load related oxidative stress and neuropathology with ingestion of daily iron supplement [31,37]. Metal metabolism is combined interplay between genes related with synthesis of metalloenzymes and dietary metal supplement.…”
Section: Neurodegenerative Diseases and Oxidative Stressmentioning
confidence: 99%
“…Tuberculosis also has been associated with increased dietary iron [67]. Similar to experimental murine models, tissue iron overload in some African populations (also known as African iron overload) resulting from increased dietary intake of iron or non-HFE hemochromatosis is positively associated with morbidity and mortality from pulmonary tuberculosis [67-70]. Finally, the efficacy of commonly used antimycobacterial drugs is compromised in mice with iron overload [59].…”
Section: Global Diseases Influenced By Iron Statusmentioning
confidence: 99%
“…Iron overload in Africa occurs as a result of consuming a traditional fermented beverage with high iron content; thus, it has been perceived as having an environmental etiology (125). However, an interaction between the iron intake from diet and a non-HLAlinked iron loading gen may contribute toward the pathogenesis of dietary iron overload (126). In an experimental study on long-evans cinnamon (LEC) rats which have been found to store abnormally high amount of iron in the liver, Kato and others in 1996 compared developing hepatitis and liver cancers in LEC rats given an iron-deficient diet (ID) with the occurrence of these diseases in rats given a regular diet (RD) (127).…”
Section: Liver Cancermentioning
confidence: 99%